Zur textuellen Grundlage des altpreußischen Enchiridions bei Trautmann (1910) - Dini, Pietro U. (Baltistica, 2020)
Basing on the new discovered copy of the OPr Enchiridion, it is possible to specify what really R. Trautmann meant in his Die altpreußischen Sprachdenkmäler (1910) with the label “Exemplar K”. Researching the clues, which are widespread in the two parts of the mentioned book, you might conclude that the copy, now at the Staatsbibliothek zu Berlin-Preußischer Kulturbesitz (Berlin, Dahlem; placement: XX HA StuB Königsberg Nr 17), corresponds to the “Exemplar K” used in Trautmann’s edition of 1910
Keywords: Old Prussian; Enchiridion; Reinhold Trautmann